It can't be true! animals - Mills, Andrea (DK, 2019)
Infographic presentation of facts and information about the unusual habits and characteristics of animals, including how sperm whales sleep and animals that grow smaller instead of larger. Features fact boxes, illustrations, a glossary, and an index.